Pathological Lying: Theoretical and Empirical Support for a Diagnostic Entity. Issue 2 (16th October 2020) - Curtis, Drew A.; Hart, Christian L.
Abstract : Objective: Pathological lying, originally called "pseudologia phantastica, " has an established history within clinical practice and literature, although it has not been recognized as a psychological disorder within major nosological systems. With the movement in psychological sciences toward theory‐driven, empirically supported diagnoses, the current study sought to empirically test whether pathological lying aligned with nosological definitions and could be defined as a diagnostic entity. Methods: A total of 807 people were recruited (January to October of 2019) from various mental health forums, social media, and a university. Of those recruited, 623 completed the study. Participants responded to a lie frequency prompt, questionnaires about lying behavior, the Lying in Everyday Situations Scale, the Distress Questionnaire‐5, and demographic questions. Results: Of the participants, 13% indicated that they self‐ identified or that others had identified them as pathological liars (telling numerous lies each day for longer than 6 months). People who identified as pathological liars reported greater distress, impaired functioning, and more danger than people not considered pathological liars. Pathological lying seemed to be compulsive, with lies growing from an initial lie, and done for no apparent reason. Conclusions: The evidence supports establishment of pathological lying as a distinct diagnostic entity. A definition of pathological lying, etiological considerations, and recommendations for future research and practice are presented. HIGHLIGHTS: Pathological lying exists in a small percentage of people, for whom it causes significant distress, impaired functioning, and danger. Pathological lying, distinct from normative lying and prolific lying, has a prevalence of 8%–13%. Evidence supports establishing pathological as a diagnostic entity.